THE ROLE OF TEACHER’S GESTURE IN THE CLASSROOM (Лучшие интеллектуальные исследования, 2025)
Abstract: Non-verbal communication plays a crucial role in the dynamics of classroom interaction. Among its many components, gestures are one of the most powerful tools at a teacher’s disposal. Gestures help in clarifying meaning, managing classroom behavior, and enhancing student comprehension and engagement. This article explores the different types of gestures used by teachers, their pedagogical functions, and the psychological mechanisms through which gestures support learning. It also discusses cultural considerations, challenges, and the importance of training teachers to use gestures effectively. Drawing on empirical studies, this article concludes that the strategic use of gestures by teachers is essential for effective teaching, particularly in multilingual or foreign language learning contexts.